اﻵثار النفسية واﻻجتماعية واﻻقتصادية لإهمال الحقوق بعد الطلاق بطلب الزوجة لانتهاك تعليق الطلاق وتخفيفها: دراسة لدى أرامل بمؤسسة اﻹسكان بسيدوارجو: Psychosocial-Economic Implications and Mitigation: Post Wife Initiate Divorce Rights Neglect Due to Taklik Talak Breach among Al-Iskan Sidoarjo Widows - Nahla Abdul Rachman; Irsan; Annisa Fristyarini; Intan Meurduati Nurwidyani (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2026)
Islamic law and positive law have comprehensively regulated women's post divorce rights. However, the legal consequences for wife initiated divorce remain inadequately defined. This leads to weak realization and failure to guarantee rights, particularly in default judgments stemming from taklik talak breaches. This study aims to examine the psychosocial-economic implications of rights neglect on widows, evaluate the role of the Al-Iskan Foundation Sidoarjo as an instrument for impact mitigation, and provide a legal critique as a basis for more substantive legal reconstruction. This study contributes by bridging the gap between legal and psychosocial analyses, revealing the paradox in the application of taklik talak, and highlighting the role of social institutions in mitigating the impacts of post divorce rights neglect. Employing a normative empirical approach and qualitative methods, data were gathered through field observations and in depth interviews with eight widows and foundation administrators. Results indicate that evidentiary obstacles, ineffective execution, low community legal literacy, and the dominance of verstek judgments are primary factors hindering rights realization. Neglecting these rights traps widows in structural poverty, causing heavy workloads and financial strain during the transition period. Psychosocially, it triggers role masculinization, devaluation of self contribution, and a decline in childcare quality. As a mitigation for the impacts of rights neglect caused by weak legal guarantees, the Al-Iskan Foundation Sidoarjo serves as a social institution providing housing, basic needs, and spiritual support, offering essential stability for the affected widows.